Characterization of the mechanical properties of banana starch bioplastic (Musa paradisiaca L.) and cellulosic compounds of coffee (Coffea arabica L.) - Cabrejos Castillo, Karla Gretel (2024)
The objective was to characterize the mechanical properties of the bioplastic obtained with banana starch (Musa paradisiaca L.) and cellulosic compounds from coffee husks (Coffea arabica L.).. Starch was used in concentrations of 9, 12 and 15% and cellulose in concentrations of 2, 4 and 6%, mixing them with glycerin, acetic acid, calcium chloride and distilled water. The tensile, elongation and bending mechanical properties were characterized. The bioplastic with the highest traction was the F9 formulation (15% starch, 6% cellulose) with 2.23 N ± 0.242 and the F1 formulation (9% starch, 2% cellulose) with the lowest traction was the F1 formulation (9% starch, 2% cellulose) with 0.17 N ± 0.069; Formulation F7 (15% starch, 2% cellulose) presented the greatest elongation of 10.3 cm ± 1.528 and greatest flexion of 13.3 cm ± 1.155; and formulation F3 (9% starch, 6% cellulose) had the lowest elongation of 3.33 cm ± 0.577 and the lowest bending of 9.33 cm ± 1.155. The increase in starch concentration favors traction, elongation and bending, the increase in cellulose concentration only favors traction, disfavors elongation and is indifferent to bending.